TUBERCULOSIS: COMMON CONSISTENT EPIDEMIC PATTERNS IN RUSSIA AND BEHIND THE URALS - V. A. Krasnov; O. V. Revyakina; P. N. Filimonov; D. V. Stepanov (Туберкулез и болезни лёгких)
The article describes the attempt to find common consistent patterns in the spread of infection, typical of Russia. Actions of the Russian Tuberculosis Control Service are compared to the ones of similar services in the world. It has been shown that the comparative cost-effectiveness per one tuberculosis patient in Russia is disparate regarding the changes in epidemiological rates. Changes in quality management parameters are slow. Increase of funding for TB services without optimization of the cost structure and revision of certain positions within the service is not sufficient for successful operation.